Letter - Palmer, R. A.
030-0206-001 Telegraphic Address: "Congress Manchester" Telephone: Blackfriars 0975 (3 lines) DEPARTMENT Agriculture Education Finance Labour Legal Propaganda Publications Statistical Co-operative Union Ltd Head Office Holyoake House Hanover St Manchester 4 GENERAL SECRETARY R.A. Palmer Consulting Solicitors W.A.S. SAN GARDE LLD., MANCHESTER D.B. MURRAY, GLASGOW RS/ ML Date 8th February, 1938. Sir Walter Citrine, The Trades Union Congress General Council, Transport House, Smith Square, London. S.W.1. Dear Sir Walter, I have the pleasure to enclose herewith our account, amounting to £100. 1. 0, for Soap shipped as detailed in the invoice. No doubt you will let me have your remittance to cover this. Yours sincerely, R.A. Palmer Enclosure. 292/946/30/206